ANALISA KELAYAKAN PEMBERIAN KREDIT MOBIL DENGAN MENGGUNAKAN NEURAL NETWORK BACKPROPAGATION - Amrin Amrin (Jurnal Techno Nusa Mandiri, 2015)
Problems are often encountered in the provision of credit is to determine lending decisions to someone, while other issues are not all credit payments can run well. Among the causes are errors of judgment in making credit decisions. In this study will be used back propagation neural network method to analyze the feasibility of providing car loans. From the test results to measure the performance of the method is to use testing methods Confusion Matrix and ROC curve, it is known that the method of back propagation neural network has a value of 89% accuracy and AUC value of 0.831. This shows that the model produced, including the classification is quite good because it has the AUC values between 0.8-0.9.